A novel technology using iron in a coupled process of moderate preoxidation–hybrid coagulation to remove cyanobacteria in drinking water treatment plants. (15th March 2022) - Jin, Yan; Li, Peijie; Xu, Bing; Wang, Lin; Ma, Guangxiang; Chen, Shuhua; Tan, Fengxun; Shao, Yuanyuan; Zhang, Lijie; Yang, Zhigang; Chen, Feiyong; Li, Wenyao; et al.
Abstract: Preoxidation–coagulation is adopted by many drinking water treatment plants to enhance the removal of cyanobacteria. However, conventional technologies — such as the combination of prechlorination with Al-salt coagulation — can easily induce secondary pollution caused by cell lysis and yield unsatisfactory performance both in removal of cyanobacterial cells and metabolites and in alleviation of filter unit fouling. To solve these issues, an iron-based coupled process of moderate preoxidation–hybrid coagulation was invented. In this technology Fe(VI) can moderately oxidize algal cells, resulting in the removal of electronegative organics coating the surfaces of the cells without destroying the algae. After preoxidation, in-situ Fe(III) produced from Fe(VI) will form a highly effective hybrid coagulant by adding a low dose of chitosan quaternary ammonium salt. Combining the reduction of electrostatic repulsion between algal cells obtained from K2 FeO4 preoxidation with the enhancement of charge neutralization, polymer bridging and adsorption capability obtained from hybrid coagulation, 92.6% of Microcystis aeruginosa cells were removed and the DOC and microcystin concentrations respectively decreased from 23.54 to 7.63 mg/L and from 16.2 to 0.96 mg/L. Meanwhile the membrane fouling was markedly alleviated. Hence this new technology couples moderate preoxidation and hybrid coagulation through the Fe(VI)–Fe(III) pairing, which is safer and more effective and can thus be a better alternative for cyanobacterial removal in drinking water treatment plants. Graphical abstract: Image 1 Highlights: Fe(VI) removed superficial negative organics from algal cells without harm. Fe(III) produced from Fe(VI) form highly effective hybrid coagulant with HTCC. Moderate preoxidation and in-situ Fe(III)-HTCC hybrid coagulation were coupled. Removal of algal cells and metabolites and reduction of filter fouling were enhanced.